You Are AWESOME : How to Navigate Change, Wrestle with Failure, and Live an Intentional Life - Pasricha, Neil, author (Toronto : Simon & Schuster Canada, 2019)
From bestselling author of The Book of Awesome series comes a revelatory and inspiring book that will change the way we view failure and help us build resilience. Resilience is a skill in desperately short supply today. Neil's new approach to resilience is in the form of nine accessible, story-based, science-backed secrets that will help you keep going and going. By taking this journey with Neil as your guide, you'll learn how to navigate failure, how to positively reframe your own perceptions, and ultimately, how to become your most unbreakable, resilient, and awesome self.